2019
DOI: 10.1016/j.cell.2019.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Transient Protein-RNA Interactions Guide Nascent Ribosomal RNA Folding

Abstract: Highlights d Real-time tracking of transcription, nascent RNA folding, and protein binding d Nascent RNA folding is complicated by native long-range RNA-RNA interactions d Late-binding ribosomal proteins chaperone nascent rRNA folding early in assembly d Protein-RNA binding dynamics cooperatively decrease during ribosome assembly

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 72 publications
1
64
0
1
Order By: Relevance
“…1c, respectively). This may suggest that co-transcriptional folding of 16S rRNA in the presence of ribosomal proteins facilitated the assembly efficiency, as recently revealed 18,19 . Also note that a long-term analysis showed that R-iSAT continued for almost half a day with very slow kinetics ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 65%
“…1c, respectively). This may suggest that co-transcriptional folding of 16S rRNA in the presence of ribosomal proteins facilitated the assembly efficiency, as recently revealed 18,19 . Also note that a long-term analysis showed that R-iSAT continued for almost half a day with very slow kinetics ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 65%
“…One implication is that cellular RNA helicases or even ribosomes can recommit the fate of these translational riboswitches long after transcription has completed. As many nucleic acid folding processes are kinetically controlled, including those involving ribonucleoprotein complexes 40 , 41 , we believe this method is broadly applicable to many types of RNA and even DNA structures, as it has been demonstrated in ribozymes (e.g., Twister 23 ), RNA aptamers (e.g., Spinach and Mango 24 ) and even telomeric DNA sequences in an experimental format that mimics co-reverse transcriptional telomeric DNA folding 36 , and to the studies of nucleic acid-protein complex assemblies.…”
Section: Discussionmentioning
confidence: 99%
“…Ribosome assembly is an efficient but complicated process (Warner, 1999;Davis and Williamson, 2017). During this process, transient rRNA-RP interactions chaperone rRNA folding, which is essential for pre-rRNA processing and the following rRNA-RP assembly, and many other assembly factors have been identified (Bohnsack and Bohnsack, 2019;Duss et al, 2019;Rodgers et al, 2019;Prattes et al, 2019), indicating that assembly of ribosomes, especially heterogeneous ribosomes, is significantly more complex than previously thought. 4.…”
Section: Open Questionsmentioning
confidence: 99%